2014
DOI: 10.5530/pc.2015.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of different extracts of Mucuna pruriensseeds on hepatoma cells but not on normal hepatic cells

Abstract: Object: Cancer has become leading cause of death in India as well as world. Synthetic anticancer agents have costly and highly toxic to human body. Therefore, it is necessary to discover new therapeutic agents from natural origin for this disease. Materials and Methods: Mucuna pruriens Linn. (MP) (family Fabaceae), is widely used in folk medicine and there is no any such report on antiproliferative effects of this plant. The first objective of this study is to investigate the anticancer properties using hepato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…While searching for new HCC agents, our previous study unveiled that the MP seeds had good antiproliferative action on Huh-7 cells [ 8 ] and this plant is rich with isoquinoline alkaloid [ 9 ]. In another of our studies, one isoquinoline alkaloid, namely M1, isolated from MP seeds, showed good antiproliferative action in vitro on Huh-7 cells through 3-(4,5-dimethylthiazol-2-y1)-2,5-diphenyl tetrazolium bromide (MTT) assay [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While searching for new HCC agents, our previous study unveiled that the MP seeds had good antiproliferative action on Huh-7 cells [ 8 ] and this plant is rich with isoquinoline alkaloid [ 9 ]. In another of our studies, one isoquinoline alkaloid, namely M1, isolated from MP seeds, showed good antiproliferative action in vitro on Huh-7 cells through 3-(4,5-dimethylthiazol-2-y1)-2,5-diphenyl tetrazolium bromide (MTT) assay [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Natural products have been used for the treatment of hepatic cancer from ancient times but very few compounds isolated till date from natural origin are effective against hepatic cancer [ 7 ]. Our previous studies demonstrated that the ethyl acetate and methanol extracts of Mucuna pruriens (MP) seeds have potent antiproliferative action on human hepatoma cell line (Huh-7 cells) [ 8 ]. Recent investigation revealed that the seeds of MP are rich with isoquinoline alkaloids [ 9 ] and these alkaloids have a dramatic role in anticancer therapy [ 10 , 11 ].…”
mentioning
confidence: 99%
“…The enzyme levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), lactate dehydrogenase (LDH), and alkaline phosphatase (ALP) were measured in serum by using commercially available kits (Yadav et al, 2015;Chauhan et al, 2017;Rai et al, 2018). Catabolic byproducts, including biliverdin and bilirubin, were identified in the liver tissue (Miranda et al, 2001).…”
Section: Estimation Of Physiological Parametersmentioning
confidence: 99%
“…Ethyl acetate and methanol extracts of M. pruriens inhibited the proliferation of hepatoma cells in vitro with a concentration at 1 μg/mL. 23 However, another study reported that the aqueous and ethanolic extracts of M. pruriens seed has no toxicity to human cervix adenocarcinoma (HeLa) cells when tested using 50 µg/mL of it. 24 Reactive oxygen and nitrogenous species generated from cellular metabolism are detrimental to our health.…”
Section: Total Phenolic and Flavonoid Contentmentioning
confidence: 99%